International labour organisation (ILO) - Kumar, Jinender (New Delhi, 2008)
The task of employment generation requires concerted action by several departments of government at the national level. But it is not a task for governments alone. Employers' and workers' organisations, as well as other members of civil society must play an increasingly active role in the process. The support of the international community is also critical, not only in terms of resource flows, but in changing the rules of international economic systems in favour of poor producers and consumers. The book covers various aspects of the issues relating to the working and performance of the ILO. It also articulate the problem of developed and developing countries in general and those of India in particular. This book usefuly for all faculty members and students of management, professionals -and policy planners. Every effort has been made to present the discussion is clear, and in systematic manner. The presentation of each chapter has been made more logical, starting with basic issues of each topic and then moving on to refined matters.
Keywords: International Labour Organization